A Multifunctional "Halide‐Equivalent" Anion Enabling Efficient CsPb(Br/I)3 Nanocrystals Pure‐Red Light‐Emitting Diodes with External Quantum Efficiency Exceeding 23%. Issue 8 (22nd December 2022) - Zhang, Jibin; Zhang, Tiankai; Ma, Zhuangzhuang; Yuan, Fanglong; Zhou, Xin; Wang, Heyong; Liu, Zhe; Qing, Jian; Chen, Hongting; Li, Xinjian; Su, Shijian; Xie, Jianing; et al.
Abstract: Pure‐red perovskite LEDs (PeLEDs) based on CsPb(Br/I)3 nanocrystals (NCs) usually suffer from a compromise in emission efficiency and spectral stability on account of the surface halide vacancies‐induced nonradiative recombination loss, halide phase segregation, and self‐doping effect. Herein, a "halide‐equivalent" anion of benzenesulfonate (BS – ) is introduced into CsPb(Br/I)3 NCs as multifunctional additive to simultaneously address the above challenging issues. Joint experiment‐theory characterizations reveal that the BS – can not only passivate the uncoordinated Pb 2+ ‐related defects at the surface of NCs, but also increase the formation energy of halide vacancies. Moreover, because of the strong electron‐withdrawing property of sulfonate group, electrons are expected to transfer from the CsPb(Br/I)3 NC to BS – for reducing the self‐doping effect and altering the n‐type behavior of CsPb(Br/I)3 NCs to near ambipolarity. Eventually, synergistic boost in device performance is achieved for pure‐red PeLEDs with CIE coordinates of (0.70, 0.30) and a champion external quantum efficiency of 23.5%, which is one of the best value among the ever‐reported red PeLEDs approaching to the Rec. 2020 red primary color. Moreover, the BS – ‐modified PeLED exhibits negligible wavelength shift under different operating voltages. This strategy paves an efficient way for improving the efficiency and stability of pure‐red PeLEDs. Abstract : Pure‐red PeLEDs based on CsPb(Br/I)3 NCs that simultaneously offer high brightness and high efficiency are demonstrated via reducing self‐doping effect, suppressing phase separation, and passivating uncoordinated Pb 2+ related defects by using a multifunctional "halide‐equivalent" benzenesulfonate anion passivation technique. The pure‐red PeLEDs exhibit a high brightness of 1510 cd m −2, a peak external quantum efficiency of 23.5%, and decent electroluminescence spectral stability.